ENHANCING MATHEMATICAL UNDERSTANDING THROUGH MODERN TECHNOLOGICAL METHODS - Alijonov Sirojiddin Husan o'g'li (Journals Park Publishing, 2025)
In recent years, the integration of modern technologies into the field of mathematics has revolutionized the way mathematical concepts are taught, learned, and applied. This article explores the various methods based on modern technologies that have been employed to enhance mathematical understanding and problem-solving skills. From interactive simulations and visualization tools to computer algebra systems and online platforms, these innovative approaches have not only made mathematics more accessible but also more engaging for learners of all ages. By leveraging technology to supplement traditional teaching methods, educators can cater to diverse learning styles and promote a deeper understanding of mathematical concepts. This article highlights the benefits of incorporating modern technological methods in mathematics education and discusses the implications for future research and practice.
Keywords: Mathematics education, modern technologies, interactive simulations, computer algebra systems, online platforms, adaptive learning.